Analysis of The Molar Volume as A Function of Pressure Close to The Melting Point in Ammonia Solid III - YURTSEVEN, H.; CAGLAR, O. (Asian Journal of Chemistry, 2010)
This study gives the calculation of the molar volume as a function of pressure for constant temperatures in ammonia solid III near the melting point. Using the value of the critical exponent γ extracted from the experimental data for the isothermal compressibility κT. The molar volume calculated here decreases as the pressure increases on approach to the melting point. This critical behaviour can describe the observed behaviour of the molar volume near the melting point, as obtained experimentally in ammonia solid III.